The segmentation of moral judgment of adolescent students in Germany : findings and problems - Beck, Klaus [Verfasser] (My University, 1998)
"The Kohlberg theory of moral development states that the individual's competence of judging moral issues is a 'structured whole'. This implies that a person well established on one of the six stages generates internally consistent moral judgments across varying contents. An alternative to this 'homogeneity postulate' is provided by the 'heterogeneity postulate' conceding that, at a given point in time, an individual may produce judgments on different stages depending on the context of the moral problems involved. This paper offers an approach to clarify and sharpen the concept of heterogeneity, i.e. the segmentation hypothesis, in order to make it accessible to empirical testing. Two studies on adolescents are reported (the second with a longitudinal design being in progress) presenting findings on individual moral judgment differences and also on conditions under which they emerge. Some implications as to related practical problems, namely the moral education trilemma, are discussed." (Autorenreferat, BIBB-Doku)
Keywords: G 1.3.3.4 Wiedereingliederung; P 1.6 Behinderte; S 2.3.1 Modellversuche in der Berufsbildung; I 2.1.1 Neue Bundesländer; Berufliche Rehabilitation; Förderung; Berufsförderung; Prüfung; Berufsausbildung; Modellversuch; Elektroberuf; Berufliche Integration; Berufliche Reintegration; Berufsbildungswerk; Lernbehinderung; Menschen mit Behinderung; Psychische Behinderung; Quantitative Angaben; Ostdeutschland